2018
DOI: 10.30958/ajspo.5-4-2
|View full text |Cite
|
Sign up to set email alerts
|

Always Together: How Football Clubs Want Constant Connections with Fans

Abstract: Football clubs represent communities; however, commercialisation and professionalization of the game pushed away these traditional links. At the present, clubs are able to control the flux of communication, employing media consultants, public relations and producing their own content. For the past decades, symbolic elements became important inside organisations: brand building and storytelling tools became key elements for economic success. Thus, sports organisations have to put in place marketing and communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The economics of football analyze the behavior of consumers (fans) and producers (clubs). Examples of studies focusing on fans/spectators include Abdel-Naby Ibrahim (2014), Binjwaied et al (2015), Borges (2018), Desbordes (2020, 2021), Harasta (2021), Özgen andArgan (2017), andPfeffel et al (2017).…”
Section: A Brief Review Of Selected Football Studiesmentioning
confidence: 99%
“…The economics of football analyze the behavior of consumers (fans) and producers (clubs). Examples of studies focusing on fans/spectators include Abdel-Naby Ibrahim (2014), Binjwaied et al (2015), Borges (2018), Desbordes (2020, 2021), Harasta (2021), Özgen andArgan (2017), andPfeffel et al (2017).…”
Section: A Brief Review Of Selected Football Studiesmentioning
confidence: 99%
“…Bachan and Reilly (2016) compare 48 European football leagues with the one in Ireland and found that the Irish clubs are supported by fans as much as in the other European leagues. Borges (2018) looks at how football clubs can build constant relations with their fans. He argues that clubs represent communities 5 and as such, the football clubs employ communication and media consultants to improve their relationships with their fans.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the media stations belonging to the clubs have a poetic function. For interaction purposes, these channels train and support a community of fans (Vannier Borges, 2018). A similar study suggested that fans and supporters are not only crucial actors in implementing the sports service but also play an important role in influencing the choices and behaviours of the football club and other stakeholders (Zagnoli & Radicchi, 2010).…”
mentioning
confidence: 98%